Surgical management of middle and distal third fractures of scaphoid fixed with Herbert screw by volar approach - Reddy, K. Vijaya Bhaskar; Chary, N. Brahma; Kumar,, C. Anil (International Journal of Research in Orthopaedics, 2021)
Surgical treatment of scaphoid fractures has evolved over the years to include variety of procedures and techniques. However scaphoid middle and distal third fractures fixation with Herbert screw by means of volar approach is a safe and effective method with good functional outcome and union rates. Our study concluded that management of middle and distal third scaphoid fractures with Herbert screw by volar approach gives excellent results in terms of union and recovery to daily activities. The wrist function improvement is more satisfactory, and the incidence of complications is low with this modality of treatment.